Upaya Pengenalan Bahaya Narkoba Melalui Sosialisasi Sebagai Bentuk Pencegahan Pada Generasi Muda Di Desa Teluk, Kecamatan Secanggang, Kabupaten Langkat - Anita Khairunnisa; Muhammad Fery Prayoga; Rista Ramadhani; Yunda Ramadani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The young generation is one part of the Indonesian nation and state. The young generation is the successor to the nation's ideals, the better the quality of the young generation, the better the quality of a nation. Drug abuse is not a condition that is carried since birth, but is caused by association, environment and limited knowledge about the dangers of drugs are one of the factors causing teenagers to consume drugs. The increasing drug abuse has given rise to the urge to carry out socialization activities for the young generation in Tekuk Village, Secanggang District, Langkat Regency. The method used in this activity is the socialization method by providing material using the lecture method, providing an explanation of drug prevention for the young generation and questions and answers. The purpose of this socialization is to provide education and introduction regarding the significant negative impacts on the physical and mental health of the young generation due to drugs.